PENERAPAN MODEL PEMBELAJARAN ARIAS(ASSURANCE, RELEVANCE, INTEREST, ASSESMENT, SATISFACTION) UNTUK MENGURANGI KESALAHAN MENYELESAIKAN SOAL KELILING DAN LUAS BANGUN DATAR SISWA KELAS X SMK NEGERI 1 JEMBER TAHUN AJARAN2012/2013 - Juhayla, Azmy; Hobri, H; Sugiarti, Titik (Kadikma, 2013)
Abstract.ARIASlearning modelis a cooperative learning which consist five components. They are Assurance, Relevance, Interest, Assesment, Satisfaction. The purpose of this research are knowing application of ARIAS learning model to reduce errors of solving perimeter and area of plane problems.The kind of this research is about PTK usingqualitative approach. The method to collected data in this research usedobservation method, interview, and test. This research was conducted at SMK Negeri 1 Jember which the subject of research are students of X AP 1class academic year 2012-2013. The data of research are students’ activities and errorsof solving perimeter and area of plane problems. In the beginning of test, total precentage of students’ mistake is 98,11% with average precentage of mistake is 19,62%.In the test 1, total precentage of students’ mistake is 97,64% with average precentage of mistake is 19,53%,but at the end of test 1 there is increasing in some kind of mistakes. At the end of test 2, total precentage decreased until 45,95% with average precentage is 9,19%. Analysis of percentage of errors conclude the application of ARIAS learning model can reduce errors of solving perimeter and area of plane problems. Key Words: ARIAS learning model, errors, plane.